Taxonomic notes on the genus Tiliacea Tutt, 1896 (Lepidoptera, Noctuidae, Xylenini) with the description of a new species and a new genus - Benedek, Balázs; Babics, János (Zootaxa, 2016)
The updated checklist and a general characterisation of the species-groups of the genus Tiliacea are presented. ′′Xanthia yunnana′′ Chen, 1999 syn. nov. is moved from the genus Tiliacea and synonymised with Gortyna joannisi (Boursin, 1928). One new species, Tiliacea annamaria sp. n. is described. ′′Xanthia′′ aurantiago (Draudt, 1950) is combined into the genus Tiliacea comb. nov. and a new genus, Tuttiana gen. nov. is established for ′′Xanthia′′ xanthophylla (Hreblay & Ronkay, 1998) comb. nov. and ′′Cirrhia′′ spalvota (Benedek & Saldaitis, 2011) comb. nov.